Espacialização de concentrações hidrogeoquimicas na água subterrânea da 17ª regional de saúde de Londrina-PR - Alan Alves Alievi; José Paulo P. Pinese; André Celligoi (Confins)
This paper aims to demonstrate the results of the spatial distribution of hydrogeochemical concentrations in the groundwater of the 17th Regional Health Londrina obtained from field sampling and instrumental chemical analysis by Atomic Emission Spectrometry (ICP-AES). This spatialization aims to highlight areas that may suggest greater care on the part of public authorities to avoid potential health risks to the community arising from the consumption of groundwater with abnormal levels of chemicals such as barium (Ba), calcium (Ca) Chrome (Cr), iron (Fe), magnesium (Mn) and silicon (Si). From the occurrences found, it was found that some portions of the territory have geochemical anomalies that raise caution on the part of local governments since anomalous concentrations of these elements can promote the regional public health hazards.